Effect of thermal treatment of illite on the bioavailability of copper and zinc in the aerobic composting of pig manure with corn straw - Escobar, Maia; Ji, Jiaoyang; Wang, Yueru; Feng, Meiqin; Bao, Changjie; Ma, Jianxun; Cui, Shijia; Zang, Sihan; Zhang, Jinpeng; Zhang, Wei; Chen, Guang; Chen, Huan (Frontiers in Microbiology, 2024)
The large amount of various types of heavy metals in animal manure applied to agricultural field has caused severe threat to the ecosystems of soil environments. In this study, the effect of thermal treatment of illite on the bioavailability of copper (Cu) and zinc (Zn) in the aerobic composting of pig manure with corn straw biochar was investigated. The objectives of this study were to charac-terize the variations in the bioavailability of Cu and Zn in the aerobic composting of pig manure added with illite treated with high temperatures and to identify the relatively dominant microbes involved in the formation of humus and passivation of heavy metals in pig manure composting based on 16S rRNA high-throughput sequencing analysis. The results showed that in comparison with the raw materials of pig manure, the bioavailability of Zn and Cu in the control and three ex-perimental composting groups, i.e., group I (with untreated illite), group I-2 (with illite treated un-der 200 ºC), and group I-5 (with illite treated under 500 ºC), was decreased by 27.66% and 71.54%, 47.05% and 79.80%, 51.56% and 81.93%, and 58.15% and 86.60%, respectively. The results of 16S rRNA sequencing analysis revealed that in the I-5 group, the highest relative abundance was de-tected in Fermentimonas, which was associated with the degradation of glucose and fructose, and the increased relative abundances were revealed in the microbes associated with the formation of humus, which chelated with Zn and Cu to ultimately reduce the bioavailability of heavy metals and their biotoxicity in the compost. This study provided strong experimental evidence to support the application of illite in pig manure composting and novel insights into the selection of appropriate additives (i.e., illite) to promote humification and passivation of different heavy metals in pig ma-nure composting.